The evolution of services trade policy since the Great Recession - Ingo Borchert; Joscelyn Magdeleine; Juan A. Marchetti; Aaditya Mattoo (World Trade Organization (WTO), 2020)
Are changes in services markets provoking reform, restrictions, or inertia? To address this question, we draw upon a new World Bank-WTO Services Trade Policy Database (STPD) to analyse the services trade policies of 68 economies in 23 subsectors across five broad areas - financial services, telecommunications, distribution, transportation and professional services, respectively. Policy measures are quantified into a Services Trade Restrictions Index (STRI) following a novel, consistent and transparent framework. Building on these innovations, the paper identifies patterns of services trade policies across sectors and economies, as well as secular trends over the past decade. Higher income economies are still more open on average than developing economies, but the chronology of reform differs markedly across sectors. In telecommunications and finance, we see convergence towards greater openness driven by liberalization in the previously more restrictive developing economies. In the hitherto universally protected transport and professional services, we see policy divergence as some higher income economies pioneer reform. But while explicit restrictions are being lowered in most services sectors - in contrast to recent developments in goods trade policy - we also see greater recourse to regulatory scrutiny, especially in higher income economies. These measures could reflect legitimate prudential or security concerns, but they could also reflect recourse to less transparent forms of protection.
Keywords: F13; F14; F23; L80; O24; 330; services trade policy; investment; STRI; trade restrictions; quantification